The hour of decision : - Spengler, Oswald (A. A. Knopf, 1934)
An essay by the author of The Decline of the West, Oswald Spengler, on the need for "Prussianism" in order to save civilization from the "Coloured Peril," based on Spengler's view, just after the Naxi rise to power in 1933, that the white (European) tribes were under attack by colored races through a "war" by various political forces - enemies of the white race. Spengler's writings had a great effect on the racial thinking of Adolf Hitler. Chapters include The Political Horizon World War & New Powers The White World Revolution The Coloured World Revolution